2021
DOI: 10.1161/circresaha.120.317900
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms of Exosome-Mediated Phagocytosis of Dead Cells in Injured Heart

Abstract: Rationale: After myocardial ischemic injury, improper phagocytic clearance of dying cardiac cells and the ensuing lack of inflammation resolution results in adverse cardiac remodeling and dysfunction that might lead to heart failure. Therefore, therapeutic strategies to ameliorate immune cell phagocytic function is critical for augmenting cardiac repair after injury. Objective: To determine if mesenchymal stem cell-derived exosomes (MSC-Exo) act as opso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…BMSCs have the functions of self-renewal, multidirectional differentiation, immune regulation and paracrine [ 29 ]. Patil et al found that MSC-derived exosomes could reduce inflammation, promote angiogenesis, and decrease infarct volume in myocardial ischemic injury, which confirmed the anti-inflammatory and reparative action of MSCs [ 30 ]. In addition, our previous studies have also shown that BMSCs reduce both local pancreatic injury and systemic inflammation by repairing vascular injury and inhibiting cell necroptosis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs have the functions of self-renewal, multidirectional differentiation, immune regulation and paracrine [ 29 ]. Patil et al found that MSC-derived exosomes could reduce inflammation, promote angiogenesis, and decrease infarct volume in myocardial ischemic injury, which confirmed the anti-inflammatory and reparative action of MSCs [ 30 ]. In addition, our previous studies have also shown that BMSCs reduce both local pancreatic injury and systemic inflammation by repairing vascular injury and inhibiting cell necroptosis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs could enhance antibacterial immune responses by promoting bacterial antigen presentation from macrophage-derived EVs, which subsequently influences the adaptive immune response (45). Likewise, Patil et al also demonstrated the opsonization role of EVs in mediated phagocytosis of dead cells in the injured heart (46). The nucleic acids' EV cargo, mainly DNA and miRNAs, has also been identified to regulate innate and adaptive immune responses.…”
Section: Physiological Functions Of Evsmentioning
confidence: 99%
“…Particularly, MFGE8 enhances opsonization of myocardial debris and also activates phagocytic signaling that facilitate removal of apoptotic cells after ischemic injury. 46 Apoptotic neutrophils express different receptors (GPCR or G-protein-coupled ALX/FPR2), which are required for the functionality of pro-resolving mediators during the resolution process, such as lipoxins, resolvins, protectins. 18 SPM entities, such as resolvin D1, and aspirin-triggered lipoxins, promote clearance of leukocytes from the infarcted site, thus promote the resolution of inflammation and cardiac repair this in turn changes the phenotype of macrophages from pro-inflammatory to anti-inflammatory and initiates the pathway of resolution.…”
Section: Leukocyte Dynamics and Macrophage Directed Resolution Pathwaymentioning
confidence: 99%